Mapping the Surgical Landscape: Resonances and Divergences Between Theories of Cosmetic and Transsexual Body Modification - Pentney, Beth; Garner, T. (Atlantis, 2008)
This paper explores the limitations of the disciplinary divide between feminist studies of cosmetic surgery and trans studies of sex reassignment surgery, in order to unpack assumptions that may otherwise go unchallenged within each field. We focus on themes of conformity and transgression, and borders and identity.